Nurses on the Front Lines: Improving Adolescent Sexual and Reproductive Health Across Health Care Settings. (January 2017) - Santa Maria, Diane; Guilamo-Ramos, Vincent; Jemmott, Loretta Sweet; Derouin, Anne; Villarruel, Antonia
Abstract : N/A: Nurses care for adolescents in a variety of settings, including communities, schools, and public health and acute care clinics, which affords them many opportunities to improve adolescents' sexual and reproductive health and reduce the rates of unplanned pregnancy and sexually transmitted infections. To ensure that adolescents have access to sexual and reproductive health care (which includes both preventive counseling and treatment) in all nursing practice sites, nurses need to gain the knowledge and hone the skills required to deliver evidence-based counseling and services to adolescents and parents. Collectively, nurses can use their unique combination of knowledge and skills to make a positive impact on adolescent sexual and reproductive outcomes. Nurses have the capacity and opportunity to disseminate information about sexual and reproductive health to adolescents and their parents in communities, schools, public health clinics, and acute care settings. This article discusses the Society for Adolescent Health and Medicine's goals and recommendations, which address adolescent sexual and reproductive health as both a health care and a human rights issue.